New student literacies amid COVID-19 : international case studies - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning ;, 2021)
The COVID-19 global pandemic triggered the need to reconceptualize provisions to run an agile university at all levels. New Student Literacies amid COVID-19 explores how institutions needed to defend teaching, learning, research and innovation, and implement transdisciplinary approaches to address such complexities together with wider knowledge sharing to unlock solutions. Delving into how universities resorted to intensive use of different technological platforms and resources to ensure that learning prevails, the chapters in this edited collection demonstrate how higher education institutions evaluated and assessed teaching methods and strove to uphold the concepts of inclusion, innovation, and cooperation of higher education. Including international case studies that highlight the issues related to the impact of the COVID-19 pandemic on higher education, the authors showcase how different countries tried to cope with the sudden shift of education to the online mode of teaching and learning, and tried to resolve challenges of online mode of education, largely around the issues of digital pedagogy.